The Effectiveness of The Motorcycled-Sabhara Patrol on Zero Street Crimes in Jurisdiction of Polrestabes Makassar - Muh. Farhan Ramadhan (Police Studies Review, 2021)
This research is propelled by crime in society. It cannot be denied that the street is a crime-prone area. In (Hagan, 2013) it is claimed that the violent crime index and property crime are the most vulnerable to occur around public facilities. The number of cases of violent crimes and property crimes has consistently is in the highest ranking. Patrolling is one of the police activities carried out by members of the National Police, as an effort to prevent disturbances in security and social security, which are caused by potential disturbances, threshold for disturbances, and real disturbances by visiting, exploring, observing, supervise, pay attention to situations, and / or conditions that require the presence of the Police to carry out policing actions. (Djamin, 2015). Therefore, this research is to analyze the effectiveness of the implementation of motorcycled-patrol activities carried out by the Sabhara of Polrestabes Makassar function in preventing street crimes in the jurisdiction of the Makassar Police. This research was obtained with a qualitative method that focuses on the effectiveness of the two-wheeled patrols in Sabhara in preventing street crimes, data collection techniques by interviewing, observing, and reviewing documents, data validity using data triangulation with primary and secondary data sources and data analysis techniques in the form of reduction data, data presentation, and drawing conclusions. It was found that the prevailing description of the effectiveness of street crime preventi through the two-wheeled patrols of Sabhara at the Makassar Polrestabes which was analyzed using the effectiveness theory had not been implemented properly at the Makassar Police. The two-wheeled patrol activities have been carried out well, but there are still several factors that affect its effectiveness. However, efforts continue to be made so that the two-wheeled patrols can run effectively. Based on the results, the researcher recommends that a larger budget allocation is needed to increase the quantity of patrol implementation and workers support in the patrol team, need for special education and training on patrolling and empowering and building relationships with the surrounding community.